On the Solvability of a Problem Nonlocal in Time for a Semilinear Multidimensional Wave Equation - Kharibegashvili, S.; Midodashvili, B. (Ukrains’kyi Matematychnyi Zhurnal, 2015)
We study a nonlocal (in time) problem for semilinear multidimensional wave equations. The theorems on existence and uniqueness of solutions of this problem are proved.